Stagnation of Achievements of Indonesian Athletes at The International Level - Muammar, Eka (Journal Research of Social Science, Economics, and Management, 2025)
The policy for young athlete development and sports performance enhancement is crucial, considering Indonesia's stagnant achievements in the Olympics. The government must accelerate the implementation of Law No. 11 of 2022 on Sports and Presidential Regulation No. 86 of 2021 on the Grand Design of National Sports (DBON) into more operational derivative regulations. This Policy Paper aims to provide alternative policies for developing young athletes at the provincial, district, and city levels to improve national sports achievements in the future. The development of young athletes in regional areas is key to nurturing potential talents from an early age, ensuring they have access to facilities, sport science-based training, and high-quality competitions. By ensuring equal sports development opportunities across all regions, Indonesia can build a stronger and more sustainable foundation for success on the international stage.